Are tax havens good? Implications of the crackdown on secrecy - Alfons J. Weichenrieder; Fangying Xu (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2015)
The pressure on tax haven countries to engage in tax information exchange shows first effects on capital markets. Empirical research suggests that investors do react to information exchange and partially withdraw from previous secrecy jurisdictions that open up to information exchange. While some of the economic literature emphasizes possible positive effects of tax havens, the present paper argues that proponents of positive effects may have started from questionable premises, in particular when it comes to the effects that tax havens have for emerging markets like China and India.
Keywords: H2; H7; 330; tax haven; secrecy; tax information exchange; China; India